Formulasi Model Nilai Sortasi Panen (NSP) dan Indeks Pengutipan Brondolan (IPB) sebagai Indikator Kinerja Pemanenan Kelapa Sawit - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
This research discusses the more realistic formulation of harvested quality effectiveness (HQE) and fruit collection index (FCI) and its use as an indicator of palm oil harvesting performance. HQE and FCI that have been formulated previously no longer applicable because of some changes in the paradigm of harvesting system of harvested fruit palm oil. The purpose of this research is to explain how to formulate HQE and FCI as well as its benefit for palm oil plantation industry. This research is a quantitative and quantitative analysis, which is a scientific study to formulate the model of HQE and FCI. The data were collected by literature study and observation. The discussion is done through descriptive analysis, ie explanation about HQE and FCI and how to use it on assessment of palm oil harvesting performance. The result showed that the formulation of HQE and FCI can be done by taking into account the current FFB grading system and taking into account the fruits composition to FFB. Both can be used to measure the palm oil harvesting performance at the estate and compare them with the quality of raw materials received at the palm oil mill.